Effectiveness of community and home care programs on the quality of life of chronic disease patients - Lumastari Ajeng Wijayanti; Natalia Datu; Ria Wahyuni (Jurnal Edukasi Ilmiah Kesehatan, 2025)
Introduction: The increasing prevalence of chronic diseases such as diabetes, hypertension, and heart disease demands a more adaptive and sustainable healthcare system. Community-based care programs and home care are becoming increasingly relevant approaches to holistically improving patients' quality of life. This study aims to evaluate the effectiveness of community care and home care programs in improving the quality of life of patients with chronic diseases. Research Methodology: This study uses a quantitative approach with a quasi-experimental design. Respondents consisted of 120 patients diagnosed with chronic disease divided into two groups: intervention (receiving community care and home care for 12 weeks) and control (conventional care). Quality of life was measured using the WHOQOL-BREF instrument before and after the intervention. Results: Results showed a significant improvement in the physical, psychological, social, and environmental dimensions of quality of life in the intervention group compared to the control group (p < 0.05). The most contributing factors were active family involvement and ongoing education by community health workers. Conclusion: Community care and home care programs effectively improve the quality of life of chronic disease patients. This approach is feasible to develop as part of a long-term chronic disease management strategy, especially in areas with limited access to health facilities